THE SIGNIFICANCE OF MEDICAL BLOGS IN THE MODERN HEALTHCARE SYSTEM: COMMUNICATIVE, EDUCATIONAL, AND REPUTATIONAL ASPECTS (International journal of artificial intelligence, 2026)
This article presents a multi-aspect theoretical analysis of the phenomenon of medical blogging as a key element in the transformation of the healthcare system under conditions of global digitalization. The study substantiates the transition from the traditional paternalistic model of “doctor–patient” interaction to a modern participatory paradigm, in which the medical blog acts as the main mediator.The author examines in detail the educational function of medical blogging aimed at increasing public health literacy and effectively counteracting the “infodemic” — the uncontrolled spread of unreliable medical information. The paper analyzes psychological mechanisms of forming compliance (adherence to treatment) through digital trust, as well as deontological risks and ethical boundaries of a physician’s presence in the media space.Special attention is paid to the role of medical blogs in pediatric practice as a tool for reducing parental anxiety. The article emphasizes the necessity of integrating professional digital communication skills into the system of continuing medical education.